Effect of coating thickness on tribological properties of manganese phosphate conversion coating in different motion conditions. (December 2022) - Zang, Libin; Zhong, Qinglun; Chen, Yong; Hou, Weijie; Zhao, Baoshan; Wu, Yimin
Abstract: Three different thickness of manganese phosphate conversion coatings are obtained on the surface of low-carbon alloy steel by chemical conversion plating. The mechanical properties of the coatings are characterized by a nanoindentation test to obtain the elastic modulus and nano-hardness. And the tribological properties under different conditions are investigated by MTM and SRV testers. The lubrication state of coatings is discussed by establishing a coating-substrate contact model. The influence of particle size and mechanical properties on tribological properties is also analyzed. The results show that the mechanical properties and friction properties of coatings are affected by the thickness of the coating, which can be changed to obtain an antifriction coating suitable for friction pairs.